A Maximum Principle in Spectral Optimization Problems for Elliptic Operators Subject to Mass Density Perturbations - Lamberti, P.D.; Provenzano, L. (Eurasian Mathematical Journal, 2013)
We consider eigenvalue problems for general elliptic operators of arbitrary order subject to homogeneous boundary conditions on open subsets of the Euclidean N-dimensional space. We prove stability results for the dependence of the eigenvalues upon variation of the mass density and we prove a maximum principle for extremum problems related to mass density perturbations which preserve the total mass.